2020
DOI: 10.7717/peerj.9702
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon, nitrogen and phosphorus ecological stoichiometry shifts with tree species in subalpine plantations

Abstract: Understanding ecological stoichiometric characteristics of soil nutrient elements, such as carbon (C), nitrogen (N) and phosphorus (P) is crucial to guide ecological restoration of plantations in ecologically vulnerable areas, such as alpine and subalpine regions. However, there has been only a few related studies, and thus whether and how different tree species would affect soil C:N:P ecological stoichiometry remains unclear. We compared soil C:N:P ecological stoichiometry of Pinus tabulaeformis, Larix kaempf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
4
5
0
Order By: Relevance
“…In line with the findings of former studies, soil C/N, C/P, and N/P ratios demonstrated a decreasing tendency with soil layers in various forest ages of Acacia hybrid, which could be attributed to the same change dynamics in SC, SN, and SP (Li et al 2013;Qi et al 2020;Qiao et al 2020). Other possible reasons are the soil surface layer being easily impacted and nutrient return from the litterfall (Feng et al 2017).…”
Section: Effects Of Stand Age and Soil Depth On Soil Nutrient Stoichi...supporting
confidence: 88%
See 1 more Smart Citation
“…In line with the findings of former studies, soil C/N, C/P, and N/P ratios demonstrated a decreasing tendency with soil layers in various forest ages of Acacia hybrid, which could be attributed to the same change dynamics in SC, SN, and SP (Li et al 2013;Qi et al 2020;Qiao et al 2020). Other possible reasons are the soil surface layer being easily impacted and nutrient return from the litterfall (Feng et al 2017).…”
Section: Effects Of Stand Age and Soil Depth On Soil Nutrient Stoichi...supporting
confidence: 88%
“…Other possible reasons are the soil surface layer being easily impacted and nutrient return from the litterfall (Feng et al 2017). Soil nutrients are often initially concentrated on the top surface layer and then transported to deeper layers via water or soil animals (Qi et al 2020).…”
Section: Effects Of Stand Age and Soil Depth On Soil Nutrient Stoichi...mentioning
confidence: 99%
“…Present SOC/TP and TN/TP ratios for 0-30 cm soil depths ranged from 49.25 to 172.48 and 1.16 to 20.40, respectively. These estimated values of SOC/TP and SOC/TN are greater than the mean value of 41.94 and 4.30, respectively, reported by Kumar et al (2021), and are similar to the range 184-299 and 12.9-19.4, respectively reported by Qi et al, (2020) in Chinese mountainous ecosystem. SOC, TN, and TP availability were assumed to be primary driving factors for microbial biomass C, N, and P content dynamics.…”
Section: Tree and Understory Components C N And P Concentrations And ...supporting
confidence: 76%
“…48 and 1.16 to 20.40, respectively. These estimated values of SOC:TP and SOC:TN are greater than the mean value of 41.94 and 4.30, respectively, reported byKumar et al (2021), andJoshi and Garkoti (2023), and are similar to the range 184-299 and 12.9-19.4, respectively reported byQi et al (2020) in Chinese mountainous ecosystem. SOC, TN, and TP availability were assumed to be primary driving factors for microbial biomass C, N, and P concentration dynamics.…”
supporting
confidence: 73%